Practical Applications for Designing Soccer' Training Tasks From Multivariate Data Analysis: A Systematic Review Emphasizing Tactical Training. Issue 3 (June 2022) - Rico-González, Markel; Pino-Ortega, José; Praça, Gibson Moreira; Clemente, Filipe Manuel
Novel viewpoints have led to an understanding that good soccer performers are capable of continuous decision-making and performing excellent motor skills in a well-conditioned mental state. Our aims in this review were to (a) summarize the effects of different conditions and constraints on a soccer player's response and (b) identify potential training designs for varied soccer tasks from a multivariate perspective, emphasizing tactical training. We performed a systematic literature review according to PRISMA guidelines and identified multiple different player constraints, including model strategies for play, drills designed for varied conditions, and training regimens for the dimensions of the physical demands soccer players will face. The use of match-sized training spaces may improve physical fitness and collective tactical behavior, while smaller spaces may contribute to improving tactical behavior from micro-structures (e.g., 1 vs. 1). Pre-session exercises that accelerate the appearance of fatigue during training may help delay the onset of match fatigue and boost players' creativity. Pitch modifications (dimensions or boundary modifications), modification of game principles (defending strategies or team formations), and altering the number of players involved or coach instructions may contribute to different player improvements. Differential learning, as a non-linear pedagogy, may induce improvements in all dimensions, but especially in creative thinking.